Wrist-worn device combining PPG and ECG can be reliably used for atrial fibrillation detection in an outpatient setting - Saarinen, Harri Juhani; Joutsen, Atte; Korpi, Kirsi; Halkola, Tuomas; Nurmi, Marko; Hernesniemi, Jussi; Vehkaoja, Antti (Frontiers in Cardiovascular Medicine, 2023)
Aims The aim was to validate the performance of a monitoring system consisting of a wrist-worn device and a data management cloud service intended to be used by medical professionals in detecting atrial fibrillation (AF). Methods Thirty adult patients diagnosed with AF alone or AF with concomitant flutter were recruited. Continuous photoplethysmogram (PPG) and intermittent 30 second Lead I ECG recordings were collected over 48 hours. The ECG was measured four times a day at prescheduled times, when notified due to irregular rhythm detected by PPG, and when self-initiated based on symptoms. Three-channel Holter ECG was used as the reference. Results The subjects recorded a total of 1,415 hours of continuous PPG data and 3.8 hours of intermittent ECG data over the study period. The PPG data were analyzed by the system’s algorithm in 5-minute segments. The segments containing adequate amounts, at least 30 seconds, of adequate quality PPG data for rhythm assessment algorithm, were included. After rejecting 46 % of the 5-minute segments the remaining data were compared with annotated Holter ECG yielding AF detection sensitivity and specificity of 95.6% and 99.2%, respectively. The ECG analysis algorithm labeled 10 % of the 30-second ECG records as inadequate quality and these were excluded from the analysis. The ECG AF detection sensitivity and specificity were 97.7 % and 89.8 %, respectively. The usability of the system was found to be good by both the study subjects and the participating cardiologists. Conclusion The system comprising of a wrist device and a data management service was validated to be suitable for use in patient monitoring and in the detection of AF in an ambulatory setting.